Strategic design and high-growth firms: A case from Turkey - Sözüer, Aytuğ; Bozaykut Bük, Tuba (Springer, 2018)
This chapter focuses on the elements of entrepreneurship and high firm growth phenomenon through a case analysis. The study first defines the fundamental concepts of entrepreneurship and its use as a strategy to yield above average returns in the middle term. Then, the relevance of entrepreneurship for emerging economies as wells as how high growth firms are explained in literature are discussed. Drawing on an actual case in the pasta market, the study analyses the strategy design that works successfully. Based on the effectuation theory, the chapter aims to unfold the entrepreneurial activity and operating mechanisms in a firm, which tripled its sales within 5 years and has become one of the fastest growing firms in Turkey. The inferences of the study would have valuable implications for small and medium-sized enterprises that pursue market expansion in competitive industries.
WOS: 000444687500006
Keywords: Firm Growth; Growth; High Growth Firms